The Tuscany Integrated Supply Chain Projects 2014–2022: A New Path to Support the Agri-Food Industry - Federica Cisilino; Antonio Giampaolo; Francesco Licciardo; Matteo Orlando; Serena Tarangioli (Land, 2023)
The Integrated Supply Chain Projects (ISCP) are promoted under the framework of Rural Development Programs (RDPs). Considering the scarce literature on ISCP, the case of Tuscany, one of the Italian regions that has implemented ISCPs most aggressively, was analyzed. The aim of this work is to give evidence of the potential positive effects of ISCPs for the agricultural sector by considering the differences between ISCP beneficiaries (treated) and non-ISCP farms (non-treated). The materials used for the analysis are twofold: the Italian Rural Network database and the Italian Farm Accountancy Data Network (FADN) dataset. The analysis is based on a three-year period (2018–2020). The sample consists of 1693 farms, outliers excluded. The treated farms included in the FADN sample total 134. The variables used are both structural and economic. The statistical analysis carried out compares treated and non-treated farms using the Welch-t-test. The results show that some key variables are significant (area; labour; revenues and costs). In general, the treated farms are more likely to improve their production process through EU funding and through new investments. In conclusion, the ISCP could be a good opportunity to support the sector. This work suggests that beneficiaries could achieve higher economic performance, especially when carrying out diversified activities.